Screening of LAB-Compatible Fungi and the Effect of Corncob Substrate Concentration on D(-) Lactic Acid Production using the Multiple Parallel Fermentation (MPF) Approach: Skrining Kapang yang Kompatibel dengan BAL serta Pengaruh Konsentrasi Substrat Tongkol Jagung terhadap Produksi Asam Laktat D(-) melalui Pendekatan Multiple Parallel Fermentation (MPF) - Mufidah, Elya; Mifzal, Adib Maula; Veliska, Audrya Nasywa; Rahayu, Farida; Irawati, Maghfira Selia; Wibisono, Yusuf; Sugiarto, Yusron; Nurika, Irnia (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2025)
Biological production of D(-) lactic acid is being advanced as an eco-friendly alternative to petrochemical routes. This study optimizes D(-) lactic-acid production from corn cobs through Multiple-Parallel Fermentation (MPF), which combines a polysaccharide-degrading filamentous fungus with lactic-acid bacteria (LAB) in a single reactor. The novelty of the work lies in deploying a specific consortium of Aspergillus sp. and Leuconostoc mesenteroides for parallel fermentation of corn-cob biomass—a combination not previously reported. Three fungal isolates and three LAB strains were screened to identify the most compatible pairing. Fermentations were run at initial pH 7.0 and 39 °C with substrate concentrations of 3, 5 and 7% w/v. The 7% loading yielded the highest D(-) lactic-acid titer (14.01 % w/v), although differences among treatments were not statistically significant (p > 0.05). One-way ANOVA satisfied normality and homogeneity-of-variance assumptions, and linear regression indicated a moderate relationship between substrate concentration and lactic-acid yield (R² = 0.429). A D/L ratio exceeding 95:5 across all treatments confirmed selective D(-) isomer formation by L. mesenteroides. These results demonstrate the promise of MPF using local lignocellulosic waste as an efficient, sustainable route to D(-) lactic acid.